Existence and Monotone Iteration of Positive Pseudosymmetric Solutions for a Third-Order Four-Point BVP. (8th April 2014) - Lv, Xuezhe; Wang, Libo; Pei, Minghe
Abstract : We study the existence and monotone iteration of solutions for a third-order four-point boundary value problem. An existence result of positive, concave, and pseudosymmetric solutions and its monotone iterative scheme are established by using the monotone iterative technique. Meanwhile, as an application of our results, an example is given.